Networks and the Internationalization of Management Consulting Firms : a critical View on traditional Theory. - Laacks, Nils (Diplomica Verlag, 2010)
HauptbeschreibungAn increasing number of management consulting firms decides to expand business activities into international markets in order to stay competitive and take advantage of new possibilities associated with globalization. Numerous internationalization theories have been developed in the last forty years. This study challenges systematically the traditional approaches of internationalization and examines the role that networks play in the internationalization process of management consulting firms and the way this is being reflected in different theoretical frameworks. The main inte.